USE OF THE WEBSITE TO HELP THE TEACHING OF ANALYTICAL CHEMISTRY - Ximenes de Pinho, Antônia; da Silva Lacerda Júnior, Orivaldo (Journal of Interdisciplinary Debates, 2023)
A website or site, also in Portuguese for site or site (“from the Web” or “from the Internet”), is a set of web pages, that is, hypertexts generally accessible via the HTTP protocol on the Internet. The set of all existing public websites makes up the World Wide Web. Pages on a site are organized around a base URL, or site, where the main page resides, and generally reside in the same directory on a server. Pages are organized within the site in a hierarchy observable in the URL, although the hyperlinks between them control how the reader perceives the overall structure, which may have little to do with the hierarchical structure of the site’s files. A website for educational purposes has been used as a tool to support learning. This work aims to report the development and use of a website in the discipline of analytical chemistry at the State University of Ceará-UECE-FAEC. The methodology of the same was through the creation of the Website on the Wixsite platform, with the following email address olacerdajr.wixsite/quimicando. The same was applied in the discipline of Analytical Chemistry II, and the Analytical II of the night shift was not applied, for the purpose of comparison in teaching learning. The class that used the website was evaluated through the production of video lessons, while the class that did not use it was evaluated through traditional evaluations, tests. In addition, the class where the website was applied, a questionnaire was carried out containing the following information: 1) I consider the use of the website relevant in this discipline, 2) the website must be maintained in the next editions of the discipline, 3) The website is easy to use, 4) the instructions contained in the site help to carry out the activities. To quantify the results, at the end of the period, a knowledge test was carried out between classes A and B to compare teaching and learning in relation to the subjects covered during the period of 2016.2 of the discipline of analytical chemistry II. With the application of the website in classes A and B, it was possible to observe that the methodology applied in class A obtained a better teaching and learning response with a percentage of 20% for the first subjects and 10% for the last subjects, demonstrating that teaching learning is best absorbed with class learning and teaching. In general, the results of the evaluations of the website by the students suggest good acceptance and show this as an easy-to-use support tool for face-to-face teaching, which can contribute to teacher/student interaction through mediation in any day and time. Through the comments, the professor, even though he was not at the university, interacted with the students, evaluating their activities, and the students, in turn, had the opportunity to redo the activities, correcting their mistakes and being free to express their points of view. teacher view.